2017
DOI: 10.1167/iovs.16-20537
|View full text |Cite
|
Sign up to set email alerts
|

Editing VEGFR2 Blocks VEGF-Induced Activation of Akt and Tube Formation

Abstract: PurposeVascular endothelial growth factor receptor 2 (VEGFR2) plays a key role in VEGF-induced angiogenesis. The goal of this project was to test the hypothesis that editing genomic VEGFR2 loci using the technology of clustered regularly interspaced palindromic repeats (CRISPR)-associated DNA endonuclease (Cas)9 in Streptococcus pyogenes (SpCas9) was able to block VEGF-induced activation of Akt and tube formation.MethodsFour 20 nucleotides for synthesizing single-guide RNAs based on human genomic VEGFR2 exon 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 50 publications
1
51
0
Order By: Relevance
“…1i). As expected, aflibercept was only able to affect the VEGF induced phosphorylation of VEGFR2 24 ( Supplementary Fig. S2).…”
Section: Apratoxin S4 Inhibits the Activation Of Human Retinal Endothsupporting
confidence: 80%
“…1i). As expected, aflibercept was only able to affect the VEGF induced phosphorylation of VEGFR2 24 ( Supplementary Fig. S2).…”
Section: Apratoxin S4 Inhibits the Activation Of Human Retinal Endothsupporting
confidence: 80%
“…The four 20-nt target DNA sequences preceding a 5′-NGG PAM sequence at exon 18 in the genomic VEGFR2 locus (NC_000071.6) were selected for generating sgRNA for SpCas9 targets using the CRISPR design Web site ( http://crispr.mit.edu ; in the public domain). 13 , 19 The four target sequences were 5′-TCAGTTCCCCTTCATTGGCC-3′ (K7), 5′-AGGCTACTTGTCTATTGTCA-3′ (K8), 5′-TTCATCTGGATCCATGACGA -3′ (K9), and 5′-GGATCCAGATGAACTCCCAT-3′ (K10). The control sgRNA sequence (5′-TGCGAATACGCCCACGCGATGGG-3′) was designed to target the lacZ gene from Escherichia coli .…”
Section: Methodsmentioning
confidence: 99%
“…36 However, the ELISA for VEGFR2 revealed no significant difference (P ¼ 0.13) in VEGFR2 concentrations among the three groups, and showed that the VEGFR2 concentration was numerically greater in the control group (2.33 6 1.87 ng/mL) than in the PRP group (1.97 6 1.00 ng/mL) and IVI group (1.21 6 0.66 ng/mL). Possible mechanisms causing downregulation of VEGFR2 by IVI should be assessed in a larger number of samples from PDR patients, ideally in a randomized controlled fashion, with or without IVI.…”
Section: Discussionmentioning
confidence: 84%